Comparison of the paper‐based and electronic versions of the Dermatology Life Quality Index: evidence of equivalence. (12th June 2017) - Ali, F.M.; Johns, N.; Finlay, A.Y.; Salek, M.S.; Piguet, V.
Summary: Background: The use of patient‐reported outcome measures in electronic format has been increasing. However, these formats are usually not validated or compared with the original paper‐based formats, so there is no evidence that they are completed in the same way. Objectives: To compare the conventional paper version with a web‐based application (iPad ® ) version of the Dermatology Life Quality Index (DLQI) to assess equivalence of scores. Methods: The study employed a randomized crossover design using a within‐subjects comparison of the two formats of the questionnaire. International Society for Pharmacoeconomics and Outcomes Research (ISPOR) guidelines were followed. Participants aged over 18 years with any confirmed skin condition were recruited from a teaching hospital dermatology outpatient clinic. Expected intraclass correlation coefficient (ICC) was 0·9 (α = 0·05). Results: A total of 104 patients were recruited, median age 53·5 years (interquartile range 37·3–67·8; 43% male). The ICC showed high concordance between the total DLQI scores from paper and iPad versions (ICC 0·98; 95% confidence interval 0·97–0·99). Patients took a median of 78 s to complete the electronic version and 73 s for paper ( P = 0·008): 76% preferred the electronic version and perceived completion to take a shorter time. Conclusions: There is high concordance and thus equivalence between the iPad and paper versions of the DLQI, with an ICC of 0·98, and a clear patient preference for the iPad version. Abstract : What's already known about this topic? The use of patient‐reported outcome measures (PROs) in electronic format has been increasing. Electronic formats are usually not validated or compared with their original paper‐based formats, but are assumed without evidence to be comparable. The benefits of using electronic PROs include portability, real‐time monitoring of patients' quality of life and improved data capture. What does this study add? There is equivalence between completing the Dermatology Life Quality Index (DLQI) on paper and in an electronic format. Patients prefer the electronic format to the paper version although the electronic format takes slightly longer to complete. This equivalence testing of the electronic format of the DLQI with the paper version will reassure and encourage such use in clinical and research settings. What are the clinical implications of this work? The DLQI application (app) will increase routine assessment of quality of life with negligible addition to consultation time. The DLQI app may facilitate transfer of patient data to electronic records, potentially being incorporated into referral systems from primary care. It is hoped the results of this study will encourage validation of other patient‐reported outcome measures in electronic format in dermatology and other medical specialties. Linked Comment: Bottomley. Br J Dermatol 2017; 177 :1157–1158 . Plain language summary available online Respond to this article